2009
DOI: 10.1097/bcr.0b013e3181b487a8
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Vitamin E, Vitamin C, and Zinc Attenuates Oxidative Stress in Burned Children: A Randomized, Double-Blind, Placebo-Controlled Pilot Study

Abstract: The aim of this study was to investigate the effect of supplementation of vitamin E, vitamin C, and zinc on the oxidative stress in burned children. In a prospective double-blind placebo controlled pilot study, 32 patients were randomized as no supplementation (n = 15) or antioxidant supplementation (n = 17) groups. Supplementation consisted of the antioxidant mixture of vitamin C (1.5 times upper intake level), vitamin E (1.35 times upper intake level), and zinc (2.0 times recommended dietary allowance) admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 28 publications
3
76
0
2
Order By: Relevance
“…In addition, Barbosa (2009) reported that there were clinical benefits have been shown with reduction of oxidative stress, and improved wound healing using doses of vitamin C and E 1.5-3 times higher than recommended daily intakes. So, these findings strongly support the use of anti-oxidants in nutritional therapy for burned patients (65)(66)(67) . Moreover, Prins (2009) illustrated that, patients with TBSA greater than 30% lose 20 to 40% of copper and 10% of selenium and zinc in the first week post burns.…”
Section: Effect Of Therapeutic Dietary Regimen On Wound Healing For Psupporting
confidence: 51%
See 3 more Smart Citations
“…In addition, Barbosa (2009) reported that there were clinical benefits have been shown with reduction of oxidative stress, and improved wound healing using doses of vitamin C and E 1.5-3 times higher than recommended daily intakes. So, these findings strongly support the use of anti-oxidants in nutritional therapy for burned patients (65)(66)(67) . Moreover, Prins (2009) illustrated that, patients with TBSA greater than 30% lose 20 to 40% of copper and 10% of selenium and zinc in the first week post burns.…”
Section: Effect Of Therapeutic Dietary Regimen On Wound Healing For Psupporting
confidence: 51%
“…Again, MacKay (2003) reported that vitamin C supplementation enhanced neutrophils mortility to chemotactic stimulus and stimulation of lymphocyte transformation and decrease the length of wound healing time. This corresponds to the work done by Barbosa et al (2009) and Sahib et al (2010) who noted that the supplementation of vitamin C reduced wound healing time (25,29,68) .…”
Section: Effect Of Therapeutic Dietary Regimen On Wound Healing For Pmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not clear from the available data whether the a-tocopherol is being redistributed to other sites or whether it is being depleted (oxidized) as a result of lipid peroxidation. A study in pediatric burn patients supplemented with a combination of antioxidants (average intakes of 900 mg vitamin C/d, 400 mg vitamin E/d, and 7 mg Zn/d) resulted in a significant increase in circulating vitamin E, a decrease in malondialdehyde, and a decrease in wound healing time (36). Our previous mechanistic studies in an ovine model of burn and smoke injury showed that the injury to the lung and skin is reflected in a higher depletion of liver a-tocopherol, which suggests mobilization of vitamin E from the liver (37).…”
Section: Discussionmentioning
confidence: 99%